Perbandingan Kadar Hemoglobin Post-Transfusi Whole Blood dan Packed Red Cells Pada Pasien Post-Operasi Sectio Caesarea - Novita Nur Awaliyah; Dewi Astuti; Mike Rezeki Sugiarti; Eva Ayu Maharani; Puji Lestari (Anakes : Jurnal Ilmiah Analis Kesehatan, 2025)
Sectio Caesarea (SC) has a risk of bleeding that leads to a decrease in the mother's hemoglobin levels. Transfusion using Whole Blood (WB) and Packed Red Cells (PRC) blood components is a prosedure to increase hemoglobin levels.This study uses a cross-sectionally comparative analytical study designs on 96 secondary data from post-operative Sectio Caesarea (SC) patients who performed pre- and post-transfusion hemoglobin examination of Whole Blood (WB) and Packed Red Cells (PRC) during the period January-December 2023. The data were analyzed in the Kolmogorov-Smirnov univariat test, then in the Non-Parametric test (Mann-Whitney test) with a degree of confidence of 90%. The results obtained haemoglobin post- transfusion of Whole Blood (WB) had a range of values of 0.0 – 2.7 g/dL with an average value of 0.5 g/ dL, whereas the haemoglobin post- transfusion Packed Red Cells (PRC) had a range of value of 0.2 – 4.0 g/dL with an average of 1.6 g/dL. The result of the paired t-test Mann-Witney obtains a p value of 0,000 so that it can be decided that there is a significant difference between the results of post-transfusion hemoglobin level of Whole Blood (WB) and Packed Red Cells (PRC). It is concluded that the post-transfusion hemoglobin level of Packed Red Cells (PRC) is higher than Whole Blood (WB), so it is recommended to use Packed Red Cells (PRC) component to increase hemoglobin levels. Keywords: hemoglobin; transfusion; sectio caesarea; whole blood cells; packed red cells